Product Differentiation: the Role of Depacking, Packing and Marking in Marketing (UNWE Yearbook, 2009)
Marketing theory still pays a little attention to those elements from the third level of the product that collaborate in higher extend to turning the trade mark in a brand. At the same time more and more authors claim that trade mark must be on the focus of the marketing. That is the reason why the author aims to analyze the role of depacking, packing and marking in marketing of producers and traders in this study. This aim is prompted by the obstacle that often the depacking, package and marking is looked at as an object of regulation, but not as object of creative work. But they reveal new place for flexibility of the producers and can create advantages that make the choice of the buyers.